LAYOUT DESIGN AND DREDGING PROJECT OF TURNING BASIN AT DONGGALA PORT PALU BAY CENTRAL SULAWESI PROVINCE - William, Christian
Donggala Port in Donggala Regency, Central Sulawesi Province experienced infrastructure damage due to the 2018 earthquake and tsunami. Due to unsuitability in several environmental aspects, reconstruction was carried out to a new location at Anjungan Gonenggati. Reconstruction at Anjungan Gonenggati requires dredging work because the existing depth conditions do not meet the required design depth for the planned vessels. In this final project, the following aspect are discussed: the layout design of the turning basin, estimated dredging volume, estimated duration of dredging work, and estimated cost of dredging work. From the design results, the dimensions of the turning basin has a depth of 20.0 meters from LWS to fulfill the long-term development project of Donggala Baru Port for 20 years from 2020 to 2039, the diameter of the turning basin for the Passenger Terminal is 300.0 meters, the diameter of the turning basin for the Cargo Terminal is 225.0 meters, and seabed slope is 35°. The dredging volume calculation uses the cross-section method, resulting in an estimated dredged volume of 988.641 ???? 3. The dredging work will be carried out using 1 unit of grab dredger "Queen Elizabeth 8", and 1 unit of trailing suction hopper dredger "SORONG" with the assistance of 2 tugboats and 2 units of split hopper barges. The dredging work will be carried out for 132 days, including mobilization and demobilization with an estimated project cost of Rp92,150,941,676.24 or Rp93,209.71/???? 3.